Efficacy and safety of secukinumab in the treatment of moderate‐to‐severe plaque psoriasis: a randomized, double‐blind, placebo‐controlled phase II dose‐ranging study. (18th January 2013) - Papp, K.A.; Langley, R.G.; Sigurgeirsson, B.; Abe, M.; Baker, D.R.; Konno, P.; Haemmerle, S.; Thurston, H.J.; Papavassilis, C.; Richards, H.B.
Summary Background Conventional systemic therapies for plaque psoriasis have not fully met the needs of patients, and although current biologic treatments are generally well tolerated, concerns exist with respect to long‐term safety. Interleukin (IL)‐17A is believed to be an important effector cytokine in the pathogenesis of psoriasis and is produced by Th17 cells, a class of helper T cells that act outside the established Th1/Th2 paradigm for regulation of innate and adaptive immunity. Objectives To assess the efficacy and safety of different doses of secukinumab, a fully human anti‐IL‐17A IgG1κ monoclonal antibody, in patients with moderate‐to‐severe plaque psoriasis. Methods Patients (n = 125) were randomized 1 : 1 : 1 : 1 : 1 to receive subcutaneous doses of placebo (n = 22) or secukinumab [1 × 25 mg (n = 29), 3 × 25 mg (n = 26), 3 × 75 mg (n = 21) or 3 × 150 mg (n = 27)] at weeks 0, 4 and 8. After the 12‐week treatment period, patients entered a follow‐up period of 24 weeks. The primary efficacy outcome was at least 75% improvement from baseline in the Psoriasis Area and Severity Index score (PASI 75); secondary outcomes included the Investigator's Global Assessment (IGA) and PASI 90 and 50 response rates. Results After 12 weeks of treatment, secukinumab 3 × 150 mg and 3 × 75 mg resulted in significantly higher PASI 75 response rates vs. placebo (82% and 57% vs. 9%; P < 0·001 and P = 0·002, respectively). Higher PASI 75 response rates compared with placebo were maintained throughout the follow‐up period with these dosages [week 36, 26% (n = 7) and 19% (n = 4) vs. 4% (n = 1), respectively], with a gradual decline of PASI 75 response over time after the dosing period. IGA response rates were significantly higher in the 3 × 150 mg group vs. placebo at week 12 (48% vs. 9%; P = 0·005) and were consistently higher for the 3 × 150 mg and 3 × 75 mg groups vs. placebo at all time points from week 4 onward. The PASI 90 response rate was significantly higher in the 3 × 150 mg group vs. placebo (52% vs. 5%) at week 12 and remained higher during the follow‐up period. Secukinumab was well tolerated. Two cases of neutropenia (≤ grade 2) were reported in the 3 × 150 mg cohort. Conclusions Treatment with subcutaneous secukinumab 3 × 75 mg and 3 × 150 mg met the primary outcome of PASI 75 response achievement after 12 weeks, demonstrating efficacy in moderate‐to‐severe psoriasis.